Technology-Based Da'wah Method in Rural Communities: Study of the Delivery of Islamic Teachings at the Jamiatul Muslimin Mosque Lamongan - Bobby Rachman Santoso; Ana Zulfatul Jannah (Fakultas Dakwah Institut Dirosat Islamiyah Al-Amien Prenduan, 2023)
This study aims to find out strategies for utilizing multimedia as a means of technology-based da'wah and what are the implications of da'wah method in spreading Islamic religious teachings to rural communities with multimedia. Current technological developments must be able to be put to good use by all groups one of which is the rural community, where they are still many who do not understand the importance of multimedia today. This research method uses qualitative interviews, observations and documents as data collection. The result of his research is the da'wah strategy implemented at the Jamiatul Muslimin mosque for mad'u, namely by using multimedia, both audio or video media and DVD projectors. In addition, the spread of religious teachings through activities is also widely disseminated through social media by administrators and other members of the public. Meanwhile, the implications of da'wah method with technology-based at the Jamiatul Muslimin mosque are being able to create a new breakthrough in spreading Islamic religious teachings and creating cooperation between people so that they are able to adapt to the times. Even the existence of multimedia has a positive impact on youth to participate in da'wah activities at the mosque.